Free Compass Math Practice on Solving Formulas - Sample 15

A set of questions, with answers, on solving formulas are presented. The answers to the questions are at the bottom of the page. These questions are similar to those in the compass math test.

  1. Solve 2 x + y = 5 + 3x for x.

    A) x = 5 - y
    B) x = y + 5
    C) x = y - 5
    D) x = - 5 - y
    E) x = 5 y

  2. Solve 2 s n = s + n for s.

    A) s = 2 - 1 / n
    B) s = n(2n - 1)
    C) s = n / (2n + 1)
    D) s = n
    E) s = n / (2n - 1)

  3. Solve (2 + x) / y = x + 1 for y.

    A) y = (x + 2) / (1 + x)
    B) y = (x + 1) / (2 + x)
    C) y = (x + 2) / (x - 1)
    D) y = (x - 2) / (x - 1)
    E) y = (x + 2) / (1 - x)

  4. Solve n = (6x + 11) / (2x + 3) for x

    A) x = (3n + 11) / (6 - 2n)
    B) x = 3 n
    C) x = (3n + 11) / (6 + 2n)
    D) x = (3n - 11) / (6 - 2n)
    E) x = (3n - 11) / (6 + 2n)

  5. Solve (2 y + t) / (y - t) = 4 for y

    A) y = (2 / 5) t
    B) y = - (3 / 2) t
    C) y = - (2 / 3) t
    D) y = - (5 / 2) t
    E) y = (5 / 2) t

  6. Solve 2 M G + G / M = 2 / M for G

    A) G = 2 M2 + 1
    B) G = 2 / (2 M2 + 1)
    C) G = 1 / (2 M2 + 1)
    D) G = 2 / (2 M2 - 1)
    E) G = 2 M2

  7. The perimeter P of a rectangle of length L and width W is given by P = 2L + 2W. Express L in terms of P and W.

    A) L = P - W
    B) L = P - 2 W
    C) L = P + 2 W
    D) L = P / 2 - W
    E) L = P / 2 + W

  8. The formula to convert temperatures from Fahrenheit F to Celsius C is given by:

    C = (5 / 9) (F - 32).

    Solve the above formula for F to obtain a formula to convert Celsius C to Fahrenheit F.

    A) F = (9 / 5) C + 32
    B) F = (9 / 5) C - 32
    C) F = C + 32
    D) F = (5 / 9) C + 32
    E) F = (5 / 9) C - 32

  9. The surface area A of a cylinder of radius r and height H is given by

    A = 2 pi r2 + 2 Pi r H

    Find a formula for H in terms of A and r.

    A) H = A / 2 Pi r
    B) H = A - 2 Pi r2 - 2 Pi r
    C) H = A / 2 Pi r - r
    D) H = A / (2 Pi r2) - 2 Pi r
    E) H = A / 2 Pi r + r

  10. Solve (z + y) / (x y z) = 2 x for y.

    A) y = z / ( 2x 2 + 1)
    B) y = x / ( 2z 2 - 1)
    C) y = - z / ( 2x 2 + 1)
    D) y = z / ( 2z 2 - x)
    E) y = z / ( 2x 2z - 1)

Share
Additional Info